Implementasi Peraturan Daerah Kabupaten Banyumas Nomor 19 Tahun 2014 Tentang Perlindungan dan Pelayanan Bagi Penyandang Disabilitas (Khususnya Pemenuhan Hak Kesehatan Terhadap Penyandang Disabilitas Ganda) - Ida Arifatul Khasanah; Esti Ningrum; Agoes Djatmiko (Faculty of Law, Universitas Wijayakusuma, 2023)
Abstract This study aims to find out the implementation of Banyumas Regency Regional Regulation Number 19 of 2014 concerning Protection and Services for Persons with Disabilities (Especially the Protection and Fulfillment of Health Rights for Persons with Multiple Disabilities), and to find out the obstacles faced in the implementation of the fulfillment of the right to Health for persons with multiple disabilities. This research uses sociological juridical research methods. The collection of research data was carried out by means of field interviews and observations supported by literature studies. Data analysis in this study is descriptive qualitative. Based on the results of research and discussion, it can be concluded that Iimplementation of Banyumas Regency Regional Regulation Number 19 of 2014 concerning Protection and Services for Persons with Disabilities (Especially Protection and Fulfillment of Health Rights for Persons with Multiple Disabilities) has been implemented by The Banyumas Social and Community and Village Empowerment Office (Dinsospermasdes) with the existence of social rehabilitation and community participation of the Paguyuban Peduli Disabiltas Ganda (PPDG) through its work program that handles 95 people with multiple disabilities with a percentage of 11% of the number of people with multiple disabilities in Banyumas Regency. In the implementation of the fulfillment of health rights, there are obstacles that must be faced, namely the limited professional or competent human resources owned, data on persons with disabilities in Banyumas Regency have not been updated thoroughly, the limited budget available for the implementation of the fulfillment of the right to k health of persons with disabilities, lack of family awareness of the rights of persons with disabilities due to shame and they prefer to hide their children, limited access to information from and for people with disabilities. Keywords: Implementation of Local Regulations, Persons with Multiple Disabilities, Fulfillment of Health Rights Abstrak Penelitian ini bertujuan untuk mengetahui Implementasi Peraturan Daerah Kabupaten Banyumas Nomor 19 Tahun 2014 Tentang Perlindungan dan Pelayanan Bagi Penyandang Disabilitas (Khususnya Perlindungan dan Pemenuhan Hak Kesehatan Terhadap Penyandang Disabilitas Ganda), dan untuk mengetahui hambatan yang dihadapi dalam pelaksanaan pemenuhan hak atas Kesehatan bagi penyandang disabilitas ganda. Penelitian ini menggunakan metode penelitian yuridis sosiologis. Pengumpulan data penelitian dilakukan dengan cara studi lapangan wawancara dan observasi didukung dengan studi Pustaka. Analisis data dalam penelitian ini yaitu deksriptif kualitatif. Berdasarkan hasil penelitian dan pembahasan dapat disimpulkan bahwa Implementasi Peraturan Daerah Kabupaten Banyumas Nomor 19 Tahun 2014 Tentang Perlindungan dan Pelayanan Bagi Penyandang Disabilitas (Khususnya Perlindungan dan Pemenuhan Hak Kesehatan Terhadap Penyandang Disabilitas Ganda) telah terlaksanakan oleh Dinas Sosial dan Pemberdayaan Masyarakat dan Desa (Dinsospermasdes) Banyumas dengan adanya rehabilitasi sosial dan peran serta masyarakat Paguyuban Peduli Disabilitas Ganda (PPDG) Banyumas melalui program kerjanya yang menangani penyandang disabilitas ganda sebanyak 95 orang dengan prosentase 11% dari jumlah penyandang disabilitas ganda di Kabupaten Banyumas. Dalam pelaksanaan pemenuhan hak Kesehatan terdapat hambatan yang harus dihadapi yaitu terbatasnya sumber daya manusia yang professional atau kompeten yang dimiliki, data penyandang disabilitas di Kabupaten Banyumas belum di mutakhirkan secara menyeluruh, terbatasnya anggaran yang tersedia untuk pelaksanaan pemenuhan hak kesehatan penyandang disabilitas, kurangnya kesadaran keluarga terhadap hak penyandang disabilitas karena alasan malu dan mereka lebih memilih untuk menyembunyikan anaknya, terbatasnya akses informasi dari dan untuk kaum disabilitas. Kata Kunci: Implementasi Peraturan Daerah, Penyandang Disabilitas Ganda, Pemenuhan Hak Kesehatan